Role of diagnostic laparoscopy in comparison with CT scan finding of patients presenting with abdominal trauma-A cross-sectional study - Yadav, Shiv Shakti; Gupta, Rachna; Lalmani Singh; Anaswara Harindran M; Jain, Ekta (Asian Journal of Medical Sciences, 2023)
Background: Trauma is a critical and urgent surgical condition that we encounter on a regular basis. Blunt trauma mechanisms account for 78.9–95.6% of all injuries, with the abdomen being affected in 6.0–14.9% of all traumatic injuries. Diagnostic laparoscopy (DL) for blunt abdominal trauma (BAT) is safe and feasible. Prerequisites are the hemodynamic stability of the patient and surgical expertise in advanced laparoscopy. Aims and Objectives: To find out the role of DL in the diagnosis and management of abdominal trauma patients. Effect on the length of hospital stay and rate of reduction of non-therapeutic laparotomy in the patients with trauma abdomen. Materials and Methods: This cross-sectional study was conducted with 50 patients of abdominal trauma with pre-structured pro forma and Written informed consent. A contrast-enhanced computed tomography (CECT) scan of the abdomen was done in hemodynamically stable patient and injury was noted. Patients meeting the inclusion criteria underwent DL. Results: The duration of hospital stay was lower in laparoscopically managed patients than in laparotomy patients. Most of the patients were managed conservatively 37 (74%) and thus by reducing non-therapeutic laparotomy. Overall recovery was 86% which signifies the reduction in mortality rate with the use of DL. In this study, clear diagnosis was obtained in 88% of the cases, so the efficacy is 88%. Conclusion: Laparoscopy and CECT abdomen has an effective diagnostic and management role in patients with BAT. The therapeutic value of DL is also accepted, well appreciated, and it cannot be underestimated.